Prophetic Da'wah in Improving The Quality of The Congregation at The Jogokariyan Mosque - Setiawan, Noval; Naseer, Riffat (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2024)
This research aims to explore the role of prophetic da'wah in improving the quality of life of the congregation at the Jogokariyan Mosque, Yogyakarta. Prophetic da'wah, which is based on the values ​​of the teachings of the Prophet Muhammad SAW, involves a holistic approach in integrating the spiritual, social and economic aspects of people's lives. This research uses a qualitative method with a case study approach to explore the impact of prophetic preaching on various aspects of congregational life. Data was collected through in-depth interviews with mosque administrators, community leaders and congregants, as well as direct observation of da'wah activities in mosques. The research results show that the implementation of prophetic preaching at the Jogokariyan Mosque has had a significant positive impact, including increasing spiritual awareness, improving social relations between congregations, as well as increasing economic prosperity through economic empowerment programs initiated by the mosque. This research also found that although there are challenges in implementing prophetic preaching, such as limited resources and resistance to change, effective strategies and active participation from the congregation can overcome these obstacles. These findings provide recommendations for other mosques to adopt the principles of prophetic da'wah in an effort to improve the quality of life of the congregation as a whole.